Locke on toleration - Locke, John, 1632-1704.; Vernon, Richard, 1945- (Cambridge ; New York : Cambridge University Press, 2010)
"John Locke's Letter Concerning Toleration (1689) is one of the most widely-read texts in the political theory of toleration, and a key text for the liberal tradition. However, Locke also defended toleration more extensively in three subsequent Letters, which he wrote in response to criticism by an Anglican cleric, Jonas Proast. This edition, which includes a new translation of the original Letter, by Michael Silverthorne, enables readers to assess John Locke's theory of toleration by studying both his classic work and essential extracts from the later Letters. An introduction by Richard Vernon sets Locke's theory in its historical context and examines the key questions for contemporary political theorists which arise from this major work in the history of political thought"--
"A Letter Concerning Toleration is an English translation of a Latin work, the Epistola de Tolerantia , that John Locke wrote towards the end of the year 1685, while living - often in hiding - in the Dutch Republic. The Epistola was not however published until 1689, after Locke's return to England, and the English translation followed very shortly after. It soon met with a critical reply, in a pamphlet written by the Oxford chaplain Jonas Proast, which was to launch a polemical exchange in the course of which Locke wrote three further defences of his argument for toleration. Unlike the Epistola/Letter (hereafter: Letter ), which is intense and compactly expressed, these defences are lengthy and often repetitive. But they comprise Locke's most fully elaborated statement of his case; they are valuable, too, because the pressure of controversy led him to clarify the priorities among his arguments"--
A letter concerning toleration / Locke -- From the Second treatise (in Two treatises of government, 2nd edn, 1698) / Locke -- From An essay concerning human understanding (4th edn, 1700) / Locke -- The argument of the Letter concerning toleration, briefly considered and answered / Proast -- From A second letter concerning toleration (1690) / Locke -- From A third letter concerning toleration in defence of the Argument of the letter concerning toleration, briefly considered and answered (1691) / Proast -- From A third letter for toleration (1692) / Locke -- From A second letter to the author of the three Letters for toleration (1704) / Proast -- From A fourth letter for toleration (1704) / Locke.
Includes bibliographical references and index.
Translated from the Latin.
Description based on print version record.
Keywords: Religious tolerance -- History -- 17th century; Electronic books